Anthems of oppressed voices: a postcolonial deliberation of the South African apartheid phrase dubul’ibhunu (kill the Boer or shoot the Boer) - Mlamli Diko (Cogent Social Sciences, 2024)
Given the reality that South African colonialism and apartheid officially ended in 1994, there is a continued visibility of racial and controversial words, phrases, and sentences that prominently seek to dehumanize Black South Africans. Having said that, White South Africans are no exception to racial and controversial turmoils given the perennial use of these problematic expressions by certain senior political figures, as proven during the course of the discussions. On account of this, it could be accentuated that racial and controversial remarks subvert South Africa’s democratic and constitutional validity, alongside international human rights and legal frameworks. With this claim in mind, this article uses dubul’ibhunu (kill the Boer or shoot the Boer) as a source of data to argue that the uncautious utilization of racial and controversial expressions, as forms of apartheid language and history, has the potential to cause adversity. This is in addition to the reality that it could potentially lead to political and social instabilities. Postcolonial theory, in which I use the prefix ‘post-’ as implying the lingering elements of colonialism, is applied to uncover and problematize how dubul’ibhunu (kill the Boer or shoot the Boer) is a multifaceted linguistic phrase that is confronted by conflicting social and political ideologies. The findings underscore that while it is implausible to erase this phrase or song as part of South Africa’s affluent history, it is similarly crucial to strike a balance between retaining it and maintaining peace and amicability when using it with no possibility of causing harm.